Impact of COVID-19 on the Healthcare of Patients With Inflammatory Bowel Disease: A Comparison Between Epicenter vs. Non-epicenter Areas - Qiu, Yun; Zhang, Ying-Fan; Zhu, Liang-Ru; He, Jin-Shen; Tan, Jin-Yu; Tan, Nian-Di; Lin, Si-Nan; Lin, Xiao-Qing; Ghosh, Subrata; Chen, Min-Hu; Mao, Ren (Frontiers in Medicine, 2020)
Background and Aims The COVID-19 pandemic poses a great challenge to health care of patients with inflammatory bowel disease (IBD). The aim of the survey was to identify and describe the impact of COVID-19 on the healthcare of patients with IBD. Methods Patients with IBD from Hubei province (epicenter of COVID-19) and Guangdong province (non-epicenter), China were surveyed during 2020, covering: change of medications (steroid, immunomodulators and biologics), procedures (lab tests, endoscopy, and elective surgery), and healthcare mode (standard healthcare vs telemedicine) during one month before and after the outbreak of COVID-19. Results In total, 324 IBD patients from Guangdong province (non-epicenter) and 149 from Hubei province (epicenter) completed the questionnaire with comparable demographic characteristics. Compared to patients in Guangdong province (non-epicenter), significantly more patients in Hubei (epicenter) had delayed lab tests/endoscopy procedure (61.1%[91/149] vs. 25.3%[82/324], p<0.001), drug withdrawal (28.6%[43/149] vs. 9.3%[30/324], p<0.001) and postponed elective surgery (16.1%[24/149] vs. 3.7%[12/324], p<0.001). There were significantly more patients having delayed biologics infusions in epicenter compared to non-epicenter (60.4% [90/149] vs. 19.1% [62/324], p<0.001) The number of patients in standard face-to-face visit reduced more dramatically in Hubei province (59.1 %[88/149] vs.12.1%[18/149], p<0.001 ) than that in Guangdong province (66.4%[215/324] vs. 37.7%[124/324], p<0.001). There was an increased use of telemedicine after outbreak compared to before outbreak in Hubei province (38.9% [58/149] vs.15.4% [23/149], p<0.001), while such significant increase was not observed in Guangdong province (21.9% [71/324] vs 18.8% [61/324], p=0.38). Among all kinds of telemedicine, hospital-based online clinics and WeChat consultations were the two most used both in Guangdong province and Hubei province. Approximately two-thirds of IBD patients from both sites supported that telemedicine should be increasingly used in future medical care. Conclusions In summary, our patient-based survey study in real-world setting showed that COVID-19 resulted in a great impact on health care of patients with IBD, and such impact was more obvious in epicenter compared to non-epicenter of COVID-19. Telemedicine offers a good solution to counteract the challenges in such an unprecedented situation of COVID-19.